UPAYA MENEKAN ANGKA KEMISKINAN SERTA PEMERATAAN PENDAPATAN NASIONAL MELALUI PEMBANGUNAN EKONOMI BERBASIS ZAKAT - Dwi Ratna Indri Hapsari (Faculty of Law, University of Muhammadiyah Malang, 2016)
Poverty is a state of people who are not able to meet their needs. As a result, people cannot live a decent so that their standard of living decline. Differences of community groups with specific earnings income gaps cause problems. Therefore, the necessary role of government in equalizes the distribution of income distribution. Starting from the economic problems then came the idea of sharia, namely optimization zakat is obligatory for Muslims to remember Indonesia is the country with the largest Muslim population in the world. Indonesia is not a religious country, but a country with a predominantly Muslim, the middle ground is needed, namely the role of the state and society in the two positions together. When zakat management is conducted in accordance with Islamic law, the mandate, expediency principle, justice and the rule of law as well as integrated it can undoubtedly reduce poverty and income inequality in Indonesian.